S74 Regulation of mitochondrial transfer between airway smooth muscle cells (ASMCs): relevance to COPD. (12th November 2019) - Frankenberg Garcia, J; Xu, B; Hui, C; Chung, KF; Rodriguez, T; Michaeloudes, C; Bhavsar, PK
Abstract : Background: Mitochondria are vital organelles in mammalian cells. In addition to their canonical role in bioenergetics, mitochondria also participate in cellular communication and signalling. Recent evidence suggests that exchange of mitochondria between cells has an important role in cellular homeostasis and responses to stress. Mitochondrial transfer by stem cells has been shown to have rescue effects in models of acute lung injury, airway inflammation and stroke. Alternatively, transfer of defective mitochondria may have detrimental effects on cellular function under disease conditions. To investigate these possibilities, it is important to understand mitochondrial transfer in healthy cells and in diseases of mitochondrial dysfunction such as chronic obstructive pulmonary disease (COPD). Methods: Mitochondrial transfer was quantified between human primary airway smooth muscel cells (ASMCs) from healthy and COPD ex-smoker patients. Mitochondrial donor cells were stained with MitoTracker dyes and directly co-cultured with CellTrace-stained recipient cells. Co-cultures were exposed to transforming growth factor β (TGF-β; 1 or 10ng/ml) or cigarette smoke media (CSM; 10 or 25%), respectively. Mitochondrial transfer was quantified by flow cytometry and visualised using fluorescence microscopy. Cells that received mitochondria were separated from cells that did not by fluorescence activated cell sorting (FACS) and re-plated for assessment of: mitochondrial respiration using the Seahorse CellMitoStress Test, mitochondrial ROS (mtROS) and mitochondrial membrane potential (Δψm) using MitoSOX and TMRM dyes, respectively, and proliferation using the BrdU Assay Kit. Results: Mitochondrial transfer between ASMCs was inhibited by TGF-β (p<0.01) and stimulated by CSM (p<0.01). Transfer of mitochondria between ASMCs led to increased mitochondrial respiration, increased mtROS and Δψm and decreased cellular proliferation (p<0.01), and this effect was the same when mitochondria were donated from COPD and healthy ASMCs. Conclusions: Transfer of mitochondria occurs between ASMCs, a process regulated by inflammation and cellular stress. Mitochondrial transfer modulates mitochondrial and cellular function in ASMCs, suggesting it may be an important homeostatic mechanism. Modulating mitochondrial transfer could be an effective strategy for the treatment of conditions associated with mitochondrial dysfunction, such as COPD.